Hubungan Sindrom Fear of Missing Out (FoMO) terhadap Perilaku Konsumtif pada Mahasiswa - Nadia Putri Ayu; Desy Safitri; Sujarwo (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The rapid advancement of digital technology has brought significant changes to various aspects of life, including how individuals interact and access information. Young people, particularly university students, are among the most affected by these changes. One phenomenon that has emerged alongside the increasing use of social media is Fear of Missing Out (FoMO)—a feeling of anxiety or worry about being left out of trends, information, or social activities experienced by others. This phenomenon not only affects individuals psychologically but also has implications for students’ consumer behavior. This study aims to analyze the influence of FoMO on students’ consumptive behavior and to identify the mediating or reinforcing factors that shape this relationship. The research employs a qualitative approach, using data collection techniques through literature review from various recent and relevant sources. The findings indicate that FoMO has a significant correlation with the rise of consumptive behavior among students, especially in the context of purchasing symbolic goods that enhance one’s self-image on social media. Key factors influencing the relationship between FoMO and consumptive behavior include the level of digitalization, social dynamics such as peer pressure, and low self-control. Furthermore, the study finds that financial literacy plays an important protective role. Students with higher levels of financial literacy tend to be more capable of managing the consumptive urges triggered by FoMO. This research contributes new insights into the psychological impact of social media on students’ economic behavior. The novelty of the study lies in its in-depth analysis of the link between FoMO and student consumer behavior in the digital era, as well as the identification of relevant mediating factors. Therefore, the results of this study are expected to serve as a foundation for developing more adaptive digital and financial literacy education programs to meet the challenges of the technological era.